PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM KETERAMPILAN BATIK TULIS KAGANO DI DESA TALANG KERING, BENGKULU UTARA - Despinaya, Despinaya; Gusti , Ririn; Sofino, Sofino (Comm-Edu (Community Education Journal), 2025)
The Kagano Handwritten Batik Skills Program in Talang Kering Village, Air Napal District, North Bengkulu, aims to develop the creativity of PKK women through batik training based on local culture. This study employs a qualitative approach using a case study method, with data collected through in-depth interviews, observations, and documentation, and data analysis conducted using triangulation to ensure validity. The results show that the batik training not only enhances the technical skills of canting (batik applying) for PKK women who previously had no experience but also fosters creativity in designing original motifs and choosing colors aligned with local cultural values, such as the Rafflesia motif and Kaganga script. This activity provides participants with space to express themselves and explore creative ideas independently, consistent with the theory of divergent thinking in creativity. Additionally, the program contributes to economic empowerment, as the skills acquired open opportunities for independent businesses and additional income for the PKK women. The training also strengthens participants’ confidence and solidarity while serving as a means of preserving local culture through the inheritance of traditional motifs. Therefore, the Kagano Handwritten Batik Program not only supports the technical capacity and creativity of the participants but also promotes social-economic and cultural development at the community level. These findings emphasize the importance of non-formal education as an effective means of developing life skills and creativity in a comprehensive and sustainable manner.